THE SHRIMP AGE OF TATALIN RAPAKIVI GRANITE AT THE NORTH MARGIN OF QAIDAM BASIN - Lu X.; Wei X.; Gu D.; Sun Y.; Zhang X.; Xiao Q.; Wang X. (My University, 2007)
Tatalin rapakivi granite suite is located in Caledonian tectonic belt of the north margin of Qaidam Basin with an area of 350km2, which is the biggest rapakivi granite mass in China. The geologic age of 440 ± 14Ma is measured by the zircon SHRIMP U-Pb dating, which belongs to Caledonian period and is 30 - 50Ma later than UP-UPF eclogite, volcanic rock of island arc and subduction granite. It formed under the hinge tectonic environment of orogeny from compressional orogeny to collision extension and shows the end of Caledonian orogeny. Eclogite-volcanic rock of island arc -subduction granite-rapakivi granite commonly forms the complete cycle of the tectonic magmatic evolution at the north margin of Qaidam Basin. The discovery and accurate confirmation of Tatalin rapakivi granite are of important scientific significance to understand the tectonic evolution characteristics and physical makeup of Caledonian tectonic belt at the north margin of Qaidam Basin and provide the important evidences in lithology for explaining the tectonic evolution of Caledonian tectonic belt at the north margin of Qaidam Basin.
Keywords: CALEDONIAN OROGENY; OROGENIC BELT; RAPAKIVI GRANITE; THE NORTH MARGIN OF QAIDAM BASIN; SHRIMP AGE; Paleozoic::Silurian; Палеозой::Силурийская